Subsidies related to the diversification in agriculture in Hungary - Áldorfainé Czabadai, Lilla (Studia Mundi – Economica, 2016)
In the past few years Hungary received a huge amount of rural development subsidies. Several studies show that the aids paid by the Agricultural and Rural Development Agency was quite efficient in many cases, but the utilization of the non-agricultural diversification subsidies were not effective. In my research I examined the effect of the less-known supports especially the impact of the subsidy for diversification into non-agricultural activities. As a result I would like to explore which Hungarian settlements took the opportunity and if so, whether this action cause an evident change in the rural areas?